PENGARUH PENAMBAHAN ABU AMPAS TEBU DAN ABU CANGKANG SAWIT DENGAN BENDA UJI SILINDER TERHADAP KUAT TEKAN BETON F’C 24,9 MPA” - Rivai, Masri A; Bahri, Zainul; Yudhatama, Aziiz (Universitas Muhammadiyah Palembang, 2020)
The use of additional materials as a mixture in the manufacture of concrete is progressive. The materials used are also increasingly varied, depending on the expected results, the added material that will hopefully achieve the expected quality of the concrete is f'c 24.9 MPa This research aims to increase the percentage of concrete increase in the percentage of addition of sugar cane dust and palm shell ash.This research uses cylindrical specimens with a total of 42 specimens consisting of 2.5% and 5% bagasse ash and 0, 2.5%, 5%, 7.5%, and 10% palm shell ash as materials. alternative to the strength of the compressive strength test concrete for 28 days.Based on the results of testing the compressive strength of cylindrical concrete, it is concluded that the increase in compressive strength is the largest. can be obtained 5% bagasse ash and 5% palm shell ash with a characteristic value of f'C 26.31 Mpa for 28 daysKeywords: Concrete, bagasse ash, palm shell ash, compressive strength